Antibiogram profile and virulence signatures of Pseudomonas aeruginosa isolates recovered from selected agrestic hospital effluents - Q. Mapipa (Nature Portfolio, 2021)
Abstract Hospital wastewater (HWW) harbours diverse microbial species and a miscellany of genome that would facilitate the emergence of novel pathogen upon genome integration that manifests novel traits in infectious pathogens. The study aimed to determine the antibiogram, and virulence signatures of Pseudomonas aeruginosa (P. aeruginosa) recovered from selected agrestic hospital effluents in Eastern Cape, South Africa. Thirty-six (36) wastewater samples were collected from selected hospital drains between February 2018 and April 2018, processed and analyzed by culture-dependent methods for the isolation of P. aeruginosa. The identity confirmation of isolates was achieved by amplification of oprl and oprL genes. Antibiogram was done using standard disk diffusion technique of Kirby–Bauer as approved by CLSI 2018 guidelines. Virulence signatures (lasA, lasB, toxA, popB) among isolates were analysed using polymerase chain reaction. A total of 54 P. aeruginosa isolates were confirmed by amplification of oprl and oprL genes in the hospital wastewater effluent samples. The isolates showed a 100% susceptibility to gentamicin, amikacin and imipenem antimicrobial agents. Ceftazidime recorded the most resistance (63%) against the isolates studied. Other antibiotics had a resistance range of 7% and 35%. The MAR index among the isolates revealed a range of 0.23 and 0.38. ToxA virulence gene was detected in all isolates while popB, lasB, lasA were detected in 82%, 75% and 54% of the isolates. This study reveals P. aeruginosa isolates with virulence traits and some strains showing multiple antibiotic resistance. The multiple antibiotic resistance index (MARI) of ≥ 0.2 indicates that the some isolates may have emerged from high-risk sources, thus projecting a risk to public health. However, with the high sensitivity pattern observed among the studied isolates, most of the antibiotics used in the susceptibility tests are not at peril. Hence, the use of these antibiotics is encouraged for treatment of infection attributed to P. aeruginosa. It is also pertinent to initiate strict control and rigid antibiotics therapeutic policy with surveillance programmes for multidrug-resistant pathogens to forestall the development and transmission of resistance traits in the pathogens.